Common Health Problems of Retired Armed Forces Personnel Admitted In Combined Military Hospital - Khan, Md Mazharul Islam; Haque, Maj Ariful; Rashid, Rehnuma; Zafreen, Farzana (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: In Bangladesh there has been steady increase in aged (>60years) from 5.6% in the year 1981 to more than 7% in the year 2006 and 12% by the year 2025. In Armed Forces we have about 30 to 35% are of aged 60 years and above.Many of them are engaged in life struggle and nation-building activities. They deserve the healthy life access to all health facilities. Objectives: To assess the common health problems of the retired Armed Forces Personnel and to find out necessary steps or quantify measures. Materials and Methods: This was a descriptive type of cross sectional study conducted among the 112 retired Armed Forces Personnel who were admitted in Combined Military Hospital, Dhaka with a view to assess their health problems. The sample was selected purposively and data was collected by face to face interview. Results: The mean age of the respondents was 59.20±7.22 years. The most prevalent diseases among the respondents were hypertension (32.1%), diabetes mellitus (17.0%), bronchial asthma (13.4%), ischemic heart disease (10.7%), and cataract (8.9%). Majority of respondents (57.1%) were unemployed, 28.6% were engaged in business and 14.3% had a job in private company. The association between their health problems and present occupational status was found statistically highly significant (p<0.05). Conclusion: The most common health problems were hypertension, diabetes mellitus, bronchial asthma and ischemic heart disease among the retired Armed Forces personnel. Prevalence almost all the diseases were significantly (p<0.05) associated with employment status. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 45-47